THE INFLUENCE OF HAZARDOUS FOOD CHEMICAL USE ON COMMUNITY WELFARE FROM THE PERSPECTIVE OF UNIMED STUDENTS - YUNITA, SRI; MANIK, INDA WATI; SIMANJUNTAK, PUTRINA; SARI, MARTA; SATI, NAFFA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This study explores Universitas Negeri Medan (UNIMED) students’ perceptions of the impact of hazardous chemical use in food on community welfare. Using a quantitative descriptive approach, the research surveyed 300 students from various faculties closely related to health, economics, and education. Simple linear regression analysis revealed a significant positive correlation (coefficient = 0.578, p < 0.05) between the perceived use of hazardous chemicals in food and the perceived decline in community welfare. The R² value of 0.555 suggests that 55.5% of the variance in welfare perceptions is explained by the awareness of chemical use in food, with other factors such as government regulation and economic stability accounting for the remainder. The findings indicate that students are cognizant of the health risks and economic burdens posed by these chemicals, which affect the quality of life. This awareness underscores the importance of educational efforts in food safety and calls for stronger governmental oversight in food regulation. By raising awareness and implementing effective policies, both health and social welfare in the community could be significantly improved. ABSTRAKPenelitian ini mengeksplorasi persepsi mahasiswa Universitas Negeri Medan (UNIMED) tentang dampak penggunaan bahan kimia berbahaya dalam makanan terhadap kesejahteraan masyarakat. Dengan menggunakan pendekatan deskriptif kuantitatif, penelitian ini mensurvei 300 mahasiswa dari berbagai fakultas yang berkaitan erat dengan kesehatan, ekonomi, dan pendidikan. Analisis regresi linier sederhana menunjukkan adanya korelasi positif yang signifikan (koefisien = 0,578, p <0,05) antara persepsi penggunaan bahan kimia berbahaya dalam makanan dan persepsi penurunan kesejahteraan masyarakat. Nilai R² sebesar 0,555 menunjukkan bahwa 55,5% dari varians dalam persepsi kesejahteraan dijelaskan oleh kesadaran akan penggunaan bahan kimia dalam makanan, dengan faktor-faktor lain seperti peraturan pemerintah dan stabilitas ekonomi menjelaskan sisanya. Temuan ini menunjukkan bahwa para siswa sadar akan risiko kesehatan dan beban ekonomi yang ditimbulkan oleh bahan kimia ini, yang mempengaruhi kualitas hidup. Kesadaran ini menggarisbawahi pentingnya upaya edukasi dalam keamanan pangan dan menyerukan pengawasan yang lebih kuat dari pemerintah dalam regulasi pangan. Dengan meningkatkan kesadaran dan menerapkan kebijakan yang efektif, kesehatan dan kesejahteraan sosial di masyarakat dapat ditingkatkan secara signifikan.